ADIÇÃO DE EVA E VERMICULITA EM ARGAMASSAS DE REVESTIMENTO: ANÁLISE DO DESEMPENHO TÉRMICO - Menezes, Francisco Ygor Moreira; Souza, Sara Jamille Marques de; Gonçalves, Felipe Fernandes; Moura, Dielho Mariano Dantas de; Silva, Cicero Joelson Vieira; Santos, Robson Arruda dos (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The search for better thermal comfort in buildings has led to the need for a coating capable of isolating the temperature from the external environment to the internal as well as the heat output from the inter of the built areas. It is with this perspective that this work seeks, from the comparison between mortars with EVA and vermiculite, to determine if there was an increase in the thermal insulation of walls coated with these mortars in relation to the mortar without addition. In this way, the proportions of 1.25%, 2.50%, 3.75% and 5.00% were determined in relation to the sand mass for each addition, and then 1m x 1m walls with 2cm thickness were constructed for the coating in each percentage and their respective additions. To obtain the temperature data, a thermal camera was used in which an hourly capture was taken from 6:00 am to 11:00 a.m. for three days in order to obtain representative averages. Therefore, the use of the additions is satisfactory since there were samples that culminated in an increase of up to 107.12% more than the conventional one.